The Positive Perceptions of Technology Utilization in EFL Vocational High School Classroom From In-service and Pre-service Teachers - Wibisono, Muh Arya; Setyaningsih, Endang; Sarosa, Teguh (Institut Agama Islam Negeri (IAIN) Metro, Lampung, Indonesia, 2024)
This study describes and compares in-service and pre-service teachers’ perception and utilization of technology in the form of computer-assisted language learning (CALL) and mobile-assisted language learning (MALL) in English as a Foreign Language (EFL) Vocational High School Classroom. This research was conducted at one of the vocational high schools in Surakarta and accommodated a multiple case study. The data of the research was obtained through document analyses, interviews, and observations. This study accommodated interactive model data analysis. The findings of this study revealed that teachers show positive and negative views on technology usage in the classroom. The positive themes found in the study are familiarity, ease of use, ease of access, interest in use, and provision of various options and qualified sources while the negative themes were mostly technical problems. This study also revealed that both groups of teachers utilized technology for three main themes: (1) presenting, (2) assisting, and (3) assessing. The differences in terms of perception and utilization of technology usage between both groups teachers were revealed to be small. To conclude, while both groups hold positive views, the actual utilization of technology is still limited so that teachers should explore more on technology usage for future implementation. Keywords: CALL, EFL, MALL, Perception, Teacher